1999
DOI: 10.1002/(sici)1096-8644(1999)110:29+<189::aid-ajpa7>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

The recognition and evaluation of homoplasy in primate and human evolution

Abstract: Homoplasy has been a prominent issue in primate systematics and phylogeny for as long as people have been studying human evolution. In the past, homoplasy, in the form of parallel evolution, was often considered the dominant theme in primate evolution. Today, it receives blame for difficulties in phylogenetic analysis, but is essential in the study of adaptation. This paper reviews the history of study of homoplasy, methods of defining homoplasy, and methodological and biological factors that generate homoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 204 publications
3
72
0
Order By: Relevance
“…The mangabey phenon contrasts with the large-bodied, long-faced, predominantly terrestrial ''baboons,'' Mandrillus, Papio, and Theropithecus. The extensive homoplasy implied by the phylogenetic distribution of these ecomorphs has made African papionins a touchstone for the study of primate morphological variation and evolution (Lockwood and Fleagle, 1999;Collard and O'Higgins, 2001;Singleton, 2002;Leigh, 2007).…”
Section: Background Papionin Phylogeny and Rungwecebus Systematicsmentioning
confidence: 99%
“…The mangabey phenon contrasts with the large-bodied, long-faced, predominantly terrestrial ''baboons,'' Mandrillus, Papio, and Theropithecus. The extensive homoplasy implied by the phylogenetic distribution of these ecomorphs has made African papionins a touchstone for the study of primate morphological variation and evolution (Lockwood and Fleagle, 1999;Collard and O'Higgins, 2001;Singleton, 2002;Leigh, 2007).…”
Section: Background Papionin Phylogeny and Rungwecebus Systematicsmentioning
confidence: 99%
“…Since directly observable data on behavior or soft tissue anatomy generally do not preserve in fossil material, paleontologists often utilize the phylogenetic species concept (although this practice has been sharply criticized, e.g., Hennig [1965]; netic analysis at the species level (Harrison 1993;Trinkaus 1995;Wolpoff and Crummett 1995). For example, it is difficult to determine, in closely related taxa, whether shared characters are due to homology or homoplasy (Lockwood and Fleagle 1999;Wood 1999), or to what degree apomorphies are affected by sample size or inter-or intrapopulation variation (Hawks 2004). A more problematic issue when using cladistic analyses in modern human origins research is that groups must be separated a priori into discrete taxa as a requirement of the methodology.…”
Section: Are Species Ontologically Fuzzy?mentioning
confidence: 93%
“…Cladistic classification requires that all taxa be crisp sets, monophyletic and mutually exclusive in their morphological patterns (Eldredge and Cracraft 1980;Hennig 1966;Mayr 1981;Olsen 1978;Wiley 1981). The characters used to compare taxa are features identifiable on the skeleton either as qualitative features or quantitative measurements/ratios (Lockwood and Fleagle 1999). Cladists trace evolutionary relationships between taxa through the identification and comparison of synapomorphies, avoiding character similarity due to sympleisomorphy or homoplasy (Delson et al 1977;Forey et al 1992;Grande and Rieppel 1994;Hennig 1966;Quicke 1993).…”
Section: Are Species Episteomologically Fuzzy?mentioning
confidence: 99%
“…Previous studies of cranial morphology in the papionin taxa have suggested relatively high levels of craniomorphic homoplasy in this tribe (Fleagle and McGraw, 1999;Lockwood and Fleagle, 1999;McGraw and Fleagle, 2006;Gilbert, 2007;Gilbert et al, 2009). Phylogenetic studies based on traditional morphometric variables resulted in three primary groups of papionins initially being recognized: mangabeys, baboons, and geladas (Thorington and Groves, 1970;Jolly, 1972;Szalay and Delson, 1979;Strasser and Delson, 1987).…”
Section: Cranial Morphology and Allometry In Papionin Primatesmentioning
confidence: 99%